KEANEKARAGAMAN HERPETOFAUNA DI RESORT LEKAWAI KAWASAN TAMAN NASIONAL BUKIT BAKA BUKIT RAYA KABUPATEN SINTANG KALIMANTAN BARAT - Sardi, Muhammad; anto, Eri; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2014)
Herpetofauna is fauna group consisting of reptiles and amphibians. This study aims to determine the diversity of herpetofauna at Lekawai Resort in Area Bukit Baka Bukit Raya National Park West Kalimantan . The method of data collection was done by using Visual Encounter Survey (VES) combining with of tracking systems. Herpetofauna found as many as 35 species which are divided into 24 kinds of amphibians and 11 species of reptiles. Air humidity ranged between 81 % - 85 %, air temperature 270C - 290C, water temperature 220C - 240C and pH of water 6. Highest species diversity index in aquatic habitats by H'= 0.996 and the lowest in terrestrial habitats that H'= 0.957. The highest evenness index in aquatic habitats that are e= 0.765 and lowest in terrestrial habitats is e= 0.724. However, the similarity index value types (S) between the two habitats is obtained with a value of 0.3. The highest abundance of amphibians in class Limnonectes kuhlii ie by 18 % . Relative abundance of reptiles found in the type of class Eutropis rudis of 5.4 %. The largest Chance encounter was belonged types Limnonectes kuhlii of 0.643 individuals / hour. Keywords: Herpetofauna, species diversity, TNBBBR